PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN AUDIT TENURE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Silvia Arista; Tertiarto Wahyudi; Yusnaini Yusnaini (AKUNTABILITAS, 2018)
This study aims to obtain empirical evidence about the influence of corporate governance structure and audit tenure on the integrity of financial statements. Population ofthis research is manufacturing companies listed on Indonesia Stock Exchange starting from 2015-2017. The sample selection used purposive sampling method and retrieved 66 companies. In this research, analysis data used multiple regression method.The results show that the corporate governance structure, consisted of independent commissioners, managerial ownership and audit committees had positive and significant influence on the integrity of financial statements, but institusional ownership had no influence. Meanwhile, audite tenure had negative and significant influence on integrity of financialstatements.